Strategi pengembangan usaha “Bakso Pak Wasino” dengan pendekatan business model canvas - Ningrum, Sinta Surya; Pahlevi, Reza Widhar (CV. Kurnia Grup, 2024)
The growth of Micro, Small, and Medium Enterprises (SMEs) in Indonesia is rapidly advancing, particularly in the food sector. Many SMEs emerge, but only a few manage to endure in the long run due to various challenges and intense competition. Bakso Pak Wasino is one such SMEs that has been operating since 1997 and continues to thrive. The owner's name is Mr. Wasino, but it has been passed down to his daughter named Sinta, or myself, for continuation and development. Currently, Bakso Pak Wasino is formulating development strategies, especially in marketing. Bakso Pak Wasino has started promoting itself on social media by creating content related to its business. Marketing through social media holds great potential to reach a broader target audience. Bakso Pak Wasino is also planning its development using the Business Model Canvas (BMC) and SWOT analysis. BMC development involves nine components, including customer segments, value propositions, channels, customer relations, revenue streams, key resources, key activities, key partners, and cost structure. Development through SWOT analysis is conducted by analyzing strengths, weaknesses, opportunities, and threats. With the use of BMC and SWOT, Bakso Pak Wasino is expected to plan its development more effectively, optimize productivity, reach a wider consumer base, and increase income generation.